MUSIC LISTENING IN INTERDISCIPLINARY VIEW - Paipare, Mirdza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Very few researches focus on music as an activity and most often it is linked to music perception, therefore – music psychology. Similarly the theories on this question are developed. Interrelations between music therapy and music psychology, as well as the role of listening and music listening in music pedagogy, psychology and music therapy are little researched. The goal of this article is to intentionally draw attention to the significance of this very common thing in our everyday lives – listening – in communication, development of cognitive and phenomenological skills and abilities (perception, recognition, describing, explaining). These skills and abilities are necessary in the work of pedagogue and psychologist, and especially music therapist.